Analysis of Ability and Opportunity on Employee Performance Mediated by Work Motivation at the Humbang Hasundutan District Attorney's Office - Lengmay Simamora; Sri Rahayu; Elfitra Desy Surya (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Employee performance is a key factor in determining the quality of public sector services, including those provided by the Humbang Hasundutan District Attorney's Office as a law enforcement agency. This study aims to analyze the influence of ability and opportunity on employee performance with work motivation as a mediating variable. The study uses a quantitative approach with a survey method. The research population consists of all 77 employees of the Humbang Hasundutan District Attorney's Office, all of whom were included in the sample. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS application. The results show that ability and opportunity have a positive and significant effect on employee performance and work motivation. In addition, work motivation has a positive and significant effect on employee performance and is able to mediate the effect of ability and opportunity on employee performance. These findings indicate that improving employee performance is not only determined by individual ability, but also by adequate work opportunities and strong work motivation. Therefore, the Humbang Hasundutan District Attorney's Office needs to strengthen employee competency development, provide adequate work facilities and infrastructure, and implement organizational policies that encourage work motivation in order to improve performance in a sustainable manner.